Administrative communication and its relationship to the effectiveness of decision-making in the Executive Committee of the General Sports Federation in Lattakia - علي ديب, خلود (Latakia University Journal -Medical Sciences Series, 2023)
Communication is one of the components or elements of the establishment of the institution, and effective communication is one of the basic factors in the development of institutions, as it is an essential and important element in the decision-making process, as data is a mainstay for decisions, and the efficiency of the decision-making process depends on the type of data or information available, and the research aims to identify The level of administrative communication in the Executive Committee, as well as identifying the effectiveness of decision-making, and what is the relationship of administrative communication with the effectiveness of decision-making among workers in the Executive Committee in Lattakia, by distributing a questionnaire to (30) members of the Executive Committee. Administrative communication among employees of the Executive Committee is average, and the effectiveness of decision-making was weak. The results also indicated that there is a positive relationship between administrative communication and the effectiveness of decision-making.